A Rare Presentation in Tularemia: Inguinally Located Glandular Tularemia - Tartar, Ayse Sagmak; Akbulut, Ayhan (Galenos Yayincilik, 2017)
[Abstract Not Available]
Keywords: Tularemia; glandular tularemia; inguinal lymphadenopathy; ciprofloxacin; treatment